2017
DOI: 10.1038/s41598-017-13573-z
|View full text |Cite
|
Sign up to set email alerts
|

Rare occurrence of inflammatory bowel disease in a cohort of Han Chinese ankylosing spondylitis patients- a single institute study

Abstract: Despite a high prevalence of ankylosing spondylitis (AS) in Han Chinese, the clinical experience remains very limited in the extra-articular presentation of inflammatory bowel disease (IBD). A monocentric retrospective study was performed for the AS-associated IBD manifestation. This study analyzed AS patients fulfilling the 1984 revised New York diagnostic criteria, excluding those who had the onset of IBD before or concurrently with the diagnosis of AS, for their demographic, clinical, laboratory, radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In a study involving 988 patients with ankylosing spondylitis in east Asia, only 0.4% developed inflammatory bowel disease. 1 However, in some analyses performed in Western countries, ~5%–10% of patients with AS present with inflammatory bowel disease. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving 988 patients with ankylosing spondylitis in east Asia, only 0.4% developed inflammatory bowel disease. 1 However, in some analyses performed in Western countries, ~5%–10% of patients with AS present with inflammatory bowel disease. 2,3…”
Section: Introductionmentioning
confidence: 99%
“…reported that the occurrence of IBD in Han Chinese patients with AS was rare. ( 5 ) Therefore, we examined the IBD risk in Taiwanese patients with AS using the large Taiwan National Health Insurance Research Database (NHIRD) and compared the risk in patients with AS with that in matched comparison cohort patients without AS.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the supposition that gut and joint inflammation in SpA are intricately linked, there are salient findings that are not consistent with the hypothesis. One issue, as highlighted in the above discussion, is that the gut-joint paradigm in SpA is based on studies in cohorts of patients of European descent, but IBD is rarely comorbid in patients with SpA who are of East Asian descent: in a 2017 study of 988 Han Chinese patients with axSpA, only four patients (0.4%) had IBD, specifically ulcerative colitis 51 , and a 2019 study of the Taiwanese national health registry Box 1 | SpA and its subtypes Historically, spondyloarthritis (spA) was classified by the pattern of articular and extra-articular symptoms. Ankylosing spondylitis (As) was identified primarily using the 1984 modified New York criteria, which specifically focused on radiographic changes to the sacroiliac joint 259 .…”
Section: Reading Between the Linksmentioning
confidence: 99%